Enhanced Photocatalytic Activity of Thienyl‐Porphyrins‐TiO2 for Degradation of 4‐Nitrophenol. Issue 2 (30th October 2012) - Ma, Wangyang; Li, Jun; Liu, Jingzhou; Feng, Meng
Abstract 5‐Mono‐(2‐thienyl)‐10, 15, 20‐triphenyl porphyrin (H2MTP) and its Co(II), Cu(II), Zn(II) metalloporphyrins (CoMTP, CuMTP, ZnMTP) were synthesized and characterized spectroscopically. The corresponding Co(II), Cu(II), Zn(II) metalloporphyrins‐TiO2 photocatalysts were then prepared and characterized by means of scanning electron microscopy (SEM), energy dispersive spectrometer (EDS), UV‐vis spectra and FT‐IR. The photocatalytic activities of these photocatalysts were investigated by testing the photodegradation of 4‐nitrophenol (4‐NP) in aqueous solution under irradiation with high‐pressure mercury lamp and metal halide lamp respectively. The results indicated that these metalloporphyrins greatly enhanced the photocatalytic efficiency of bare TiO2 in degradating the 4‐NP, and CuMTP‐TiO2 exhibited the highest photocatalytic activity of all photocatalysts. In addition, the first order rate constants of these photocatalytic reactions were calculated.